Employment, Inflation and Income Distribution in an Open Economy. Pricing-to-market in a Modified NAIRU Model - Stefan Ederer (Austrian Institute of Economic Research (WIFO), 2010)
The paper modifies a standard NAIRU model by implementing "pricing-to-market" as the basic assumption for the price setting behaviour of firms in an open economy. This entirely changes the outcomes of the model: First, inflation in equilibrium is stable at any rate of unemployment; the long-run Phillips curve is horizontal. Second, income distribution varies with the level of employment. Third, supplemented with a demand equation which allows for effects of both income distribution and international competitiveness, the NAIRU ceases to be a "strong attractor". These characteristics to a certain extent open up the space for expansive wage and demand policies.
Keywords: 330; Wages; Inflation; NAIRU; Demand; Distribution; Natürliche Arbeitslosenquote; Inflation; Einkommensverteilung; Offene Volkswirtschaft; Theorie